Pengembangan Media Etnopedagogi Tari Ronggeng untuk Meningkatkan Kreativitas dan Penguatan Identitas Budaya Siswa Sekolah Dasar: Development of Ronggeng Dance Ethnopedagogy Media to Enhance Creativity and Strengthen Cultural Identity Among Elementary School Students - Salasiah Salasiah; Ganes Gunansyah; Ari Metalin Ika Puspita (ITScience (Information Technology and Science), 2026)
The limited integration of local cultural values into arts and culture learning media in elementary schools results in a learning process that remains largely theoretical and fails to provide a fully contextual learning experience. This situation restricts opportunities for students to explore their creativity and weakens their understanding of local cultural identity—a crucial element in character development. This study aims to develop learning media based on the ethnopedagogy of the Ronggeng dance to enhance creativity and strengthen the cultural identity of elementary school students. The study employs the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The research was conducted at State Elementary School (SDN) 024 Sepaku, North Penajam Paser Regency, East Kalimantan Province. Data collection techniques included observation, interviews, questionnaires, and documentation. Research instruments were validated by subject matter and media experts, followed by descriptive quantitative and qualitative analysis. The results indicate that subject matter expert validation achieved a score of 87.5% (categorized as